Brachytherapy in the treatment of patients with lung cancer - Fijuth, Jacek; Makarewicz, Roman (Contemporary Oncology/Współczesna Onkologia, 2002)
In spite of the development of oncology, the treatment results in lung cancer patients are still bad. It is necessary to look for new treatment methods. The article discusses the significance of brachytherapy in the treatment of lung cancer patients. Although standard clinical indications and dosage schedules have not been established endobronchial brachytherapy has a well-defined role in the palliative management of lung cancer patients. The emergence of high dose rate brachytherapy has improved this option. With conventional dose rate brachytherapy the source was typically left in place for 1 to 2 days and required hospitalization with the attendant disadvantages of greater expense, increased patient discomfort, and more complicated radiation protection issues. High dose rate brachytherapy let the entire treatment to be accomplished in a matter of minutes on an outpatients basis, and fractionated treatments are feasible. Several studies of endobrachial brachytherapy have demonstrated improvement in hemoptysis, cough, and dyspnea. Serious complications of high dose rate intraluminal brachytherapy, such as fistula formation, tracheal perforation, pneumonitis and radiation bronchitis are typically rare. The one more often complication is haemorrhage. However, it is often difficult to differentiate a treatment complication from the effect of tumor progression in these patients. An intriguing issue is whether there is a role for endobronchial brachytherapy as a boost in selected patients receiving definitive external beam radiotherapy. These results indicate that the role of brachytherapy as a boost in unresectable lung cancer is likely to be minor. However, in selected patients with a prominent intraluminal component, the approach may be adventageous. Endobronchial brachytherapy offers an innovative method of delivering high dose radiation to the defined volume while sparing surrounding normal structures.